SISTEM INFORMASI PENJUALAN BUKU BERBASIS WEB PADA TOKO BUKU AS-SALAM BEKASI MENGGUNAKAN PHP & MYSQL - Afnisari, Karnita; Herlawati, Herlawati; Merlina, Nita (Jurnal Pilar Nusa Mandiri, 2013)
In the time of globalization now is the development of science and technology have developed by leaps and bounds. Everything required is done quickly and accurately. It can be realized by the use of technology to its full potential. Technology, in this case, is indeed very necessary computer are included in the business world and the world of education, with the company's performance. See the increasingly rapid development. The author tried to make the information system Web-based book sales with the Use of Php & amp; MySQL On The Bookstore As-Salam Bekasi. With this web-based system to computerize the authors hope the problems existing in the company, especially in terms of data processing can be resolved properly. The information generated can be more accurate, fast and efficient. In addition to the company's web-based information systems can also be simultaneously marketed its products to the public. So everything could run with web